Straight from the bottle! Wine and juice dicarboxylic acids as templates for supramolecular cage self-assembly. Issue 78 (10th September 2021) - Begato, Federico; Penasa, Roberto; Licini, Giulia; Zonta, Cristiano
Abstract : Two imine based supramolecular cages are able to self-assemble in the presence of a complex mixture like wine or fruit juices. Abstract : Two imine based supramolecular cages are able to self-assemble in the presence of a complex mixture like wine or fruit juices. Taking advantage of templating agents present in these mixtures the systems are able to form and to selectively encapsulate dicarboxylic systems present in the mixtures. This capability has been exploited to develop molecular systems able to report the enantiomeric excess and composition of (a)chiral dicarboxylic acids in fruit juices and wines using 1 H-NMR.